Comparative analysis of rodent lens morphometrics and biomechanical properties - Cheheltani, Sepideh; Islam, Sadia T.; Malino, Heather; Abera, Kalekidan; Aryal, Sandeep; Forbes, Karen; Parreno, Justin; Fowler, Velia M. (Frontiers in Ophthalmology, 2025)
IntroductionProper ocular lens function requires biomechanical flexibility, which is reduced during aging. As increasing lens size has been shown to correlate with lens biomechanical stiffness in aging, we tested the hypothesis that whole lens size determines gross biomechanical stiffness by comparing lenses of varying sizes from three rodent species (mice, rats, and guinea pigs).MethodsCoverslip compression assay was performed to measure whole lens biomechanics. Whole mount staining on fixed lenses, followed by confocal microscopy, was conducted to measure lens microstructures.ResultsAmong the three species, guinea pig lenses are the largest, rat lenses are smaller than guinea pig lenses, and mouse lenses are the smallest of the three. We found that rat and guinea pig lenses are stiffer than the much smaller mouse lenses. However, despite guinea pig lenses being larger than rat lenses, whole lens stiffness between guinea pigs and rats is not different. This refutes our hypothesis and indicates that lens size does not solely determine lens stiffness. We next compared lens microstructures, including nuclear size, capsule thickness, epithelial cell area, fiber cell widths, and suture organization between mice, rats, and guinea pigs. The lens nucleus is the largest in guinea pigs, followed by rats, and mice. However, the rat nucleus occupies a larger fraction of the lens. Both lens capsule thickness and fiber cell widths are the largest in guinea pigs, followed by mice and then rats. Epithelial cells are the largest in guinea pigs, and there are no differences between mice and rats. In addition, the lens suture shape appears similar across all three species.DiscussionOverall, our data indicates that whole lens size and microstructure morphometrics do not correlate with lens stiffness, indicating that factors contributing to lens biomechanics are complex and likely multifactorial.